2002
DOI: 10.1300/j056v13n03_06
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pedophilia with Leuprolide Acetate

Abstract: To date, the literature on the treatment of individuals who have committed sexual offenses has focused primarily on psychotherapeutic interventions and the use of antiandrogens. Recently case reports and small series supporting the efficacy of other psychiatric medication, such as serotonin reuptake inhibitors, have been published. Only a few publications have looked at the efficacy of leuprolide acetate, an LH-RH antagonist, in treatment of sex offenders. Leuprolide acetate has advantages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Notwithstanding these limitations, results indicated that treatment with LA resulted in a significant suppression of deviant sexual interests and behavior (Krueger & Kaplan, 2001). Similarly, Raymond et al (2001) found, in their case study of a pedophilic sexual offender, that LA treatment was effective in decreasing deviant sexual fantasies, and the patient reported a dramatic reduction in his pedophilic urges. In addition, several review articles with a focus on LA as a treatment for paraphilias and/or sexual offenders have observed that, although there are notable methodological limitations to the current research base in this area, LA appears to offer a viable treatment option with fewer side effects than traditional hormonal agents (Briken, Hill, & Berner, 2003; Briken & Kafka, 2007; Rösler & Witzum, 2000; Saleh & Berlin, 2003).…”
Section: Leuprolide Acetate (La) As Sex Offender Treatmentmentioning
confidence: 85%
See 3 more Smart Citations
“…Notwithstanding these limitations, results indicated that treatment with LA resulted in a significant suppression of deviant sexual interests and behavior (Krueger & Kaplan, 2001). Similarly, Raymond et al (2001) found, in their case study of a pedophilic sexual offender, that LA treatment was effective in decreasing deviant sexual fantasies, and the patient reported a dramatic reduction in his pedophilic urges. In addition, several review articles with a focus on LA as a treatment for paraphilias and/or sexual offenders have observed that, although there are notable methodological limitations to the current research base in this area, LA appears to offer a viable treatment option with fewer side effects than traditional hormonal agents (Briken, Hill, & Berner, 2003; Briken & Kafka, 2007; Rösler & Witzum, 2000; Saleh & Berlin, 2003).…”
Section: Leuprolide Acetate (La) As Sex Offender Treatmentmentioning
confidence: 85%
“…This effect can be mitigated or cessation can be achieved through careful monitoring and medical management, including the addition of medications and supplements such as Vitamin D and Calcium (Dickey, 2002; Rösler & Witzum, 1998). There are a few reported case studies supporting the use of LA in sexual offender management (Dickey, 1992; Krueger & Kaplan, 2001; Raymond et al, 2001). Findings from small, uncontrolled studies have found support for the use of LA as a promising adjunct to sex offender treatment (Briken et al, 2001; Schober et al, 2005).…”
Section: Leuprolide Acetate (La) As Sex Offender Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific aspects of behavior that are affected by therapy, as well as the efficacy, limitations, and side effects of treatment need to be determined (Briken et al, 2003;Raymond, Robinson, Kraft, Rittberg, & Coleman, 2001). The present study assessed the impact of cognitive-behavioral psychotherapy alone versus cognitive-behavioral psychotherapy augmented with a potent testosterone-lowering drug, LA, for suppression of pedophilic urges and arousability.…”
Section: Introductionmentioning
confidence: 99%